Efficacy of a survivorship‐focused consultation versus a time‐controlled rehabilitation consultation in patients with lymphoma: A cluster randomized controlled trial. Issue 23 (18th October 2018) - Parker, Patricia A.; Banerjee, Smita C.; Matasar, Matthew J.; Bylund, Carma L.; Rogers, Madeline; Franco, Kara; Schofield, Elizabeth; Li, Yuelin; Levin, Tomer T.; Jacobsen, Paul B.; Astrow, Alan B.; Leventhal, Howard; et al.
Abstract: Background: Survivors of cancer often describe a sense of abandonment after treatment along with heightened uncertainty and limited knowledge of what lies ahead. This study examined the efficacy of a survivorship care plan (SCP) intervention to help physicians to address survivorship issues through communication skills training plus a new consultation focused on the use of an SCP for patients with Hodgkin lymphoma and diffuse large B‐cell lymphoma. Methods: This 4‐site cluster randomized trial examined the efficacy of a survivorship planning consultation (SPC) in patients who achieved complete remission after the completion of first‐line therapy (for the SPC, physicians received communication skills training and, using an SCP, applied those skills in a survivorship‐focused office visit) versus a control arm in which physicians were trained in and subsequently provided a time‐controlled, manualized wellness rehabilitation consultation (WRC) focused only on discussion of healthy nutrition and exercise as rehabilitation after chemotherapy. The primary outcomes for patients were changes in knowledge about lymphoma and adherence to physicians' recommendations for vaccinations and cancer screenings. Results: Forty‐two physicians and 198 patients participated across the 4 sites. Patients whose physicians were in the SPC arm had greater knowledge about their lymphoma ( P = .01) and showed greater adherence to physician recommendations for influenza vaccinations ( P = .02) and colonoscopy ( P = .02) than patients whose physicians were in the WRC arm. Conclusions: A dedicated consultation using an SCP and supported by communication skills training may enhance patients' knowledge and adherence to some health promotion recommendations. Abstract : This study examines the efficacy of a survivorship care planning intervention to help physicians to address survivorship issues through a new consultation focused on the use of a survivorship care plan for patients with Hodgkin lymphoma and diffuse large B‐cell lymphoma. A dedicated consultation using a survivorship care plan and supported by communication skills training enhances patients' knowledge and adherence to health promotion recommendations.